Sweet basil (Ocimum basilicum L.) flowering affected by foliar nitrogen application - Renata Nurzyńska-Wierdak (Acta Agrobotanica, 2012)
The aromatic and curative properties of basil are connected with the presence of essential oil, mainly in the leaves and flowers. Herb yield and the quality of basil oil are related to the effect of genetic, ontogenetic and environmental factors. In the studies conducted in the years 2008-2009, the effect of basil cultivar and foliar feeding upon selected flowering features was examined. In an unheated plastic tunnel, plants of Kasia, Wala, Genua Star and Opal cultivars were grown. Foliar feeding was done by the application of 0.5% urea solution or by spraying the plants with water. During harvest the characteristic features of flowering were determined, i.e. the number and length of inflorescences, as well as the number of verticils and flowers per inflorescence. A vast differentiation was demonstrated in flowering of sweet basil plants of the examined cultivars. The most inflorescences were formed by the plants of the Polish cultivar Kasia, compared to the remaining ones. The longest inflorescences with the highest number of flowers in the main inflorescence were found in 'Genua Star'. Foliar feeding of the plants with nitrogen caused a significant increase of inflorescence number, but it did not significantly affect the remaining features of basil flowering.